(untitled) (World Bulletin of Public Health, 2025)
Cardiac asthma is an acute manifestation of left ventricular heart failure characterized by pulmonary interstitial and alveolar edema. It presents clinically with sudden onset dyspnea, orthopnea, tachycardia, and cyanosis. This article discusses the key etiological factors, clinical features, differential diagnosis, and resuscitative management of cardiac asthma